1988
DOI: 10.1111/j.1529-8817.1988.tb00189.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Silicon Deficiency on Lipid Composition and Metabolism in the Diatom Cyclotella Cryptica

Abstract: The effects of silicon deficiency on the metabolism and composition of lipids i n Cyclotella cryptica T 1 3 L Reimann, Lewin, and Guillard were examined. Silicon-deficient cells had higher levels of neutral lipids (primarily triacylglycerols) and higher proportions of saturated and monounsaturated fatty acids than silicon-replete cells. After 4 h of silicon deficiency, the percentage of newly assimilated NaH14C0, partitioned into lipids increased from 27.6% to 54.1 %, whereas the percentage partitioned into ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(65 citation statements)
references
References 17 publications
2
63
0
Order By: Relevance
“…P. tricorntum had a 2-fold increase in fatty acid content but reduced in a half in biomass production under phosphorus starvation environment (Wurch et al, 2011). In most diatom species, silicon is one key component of cell wall structure and therefore a limiting micro-nutrient for diatom biomass production (Roessler, 1988). The acetyl-CoA carboxylase activity was enhanced by 2-fold and 4-fold respectively after 4 and15 h growth without silicate in Cyclotella cryptica (Roessler, 1988).…”
Section: Environmental Stimulantsmentioning
confidence: 93%
“…P. tricorntum had a 2-fold increase in fatty acid content but reduced in a half in biomass production under phosphorus starvation environment (Wurch et al, 2011). In most diatom species, silicon is one key component of cell wall structure and therefore a limiting micro-nutrient for diatom biomass production (Roessler, 1988). The acetyl-CoA carboxylase activity was enhanced by 2-fold and 4-fold respectively after 4 and15 h growth without silicate in Cyclotella cryptica (Roessler, 1988).…”
Section: Environmental Stimulantsmentioning
confidence: 93%
“…Factoring this into DCW measurements, this suggests that lipid content in diatoms on a per cell carbon basis is substantially higher than usually reported. Illustrating this point is a comparison of Si-induced lipid accumulation in C. cryptica, in which total lipid based on DCW was 42% [97] compared with 54.1% when calculated on an AFDW basis [109]. The data suggest that diatoms are at least on par with, if not superior to, other classes of algae in terms of their ability to accumulate lipids.…”
Section: Key Termmentioning
confidence: 99%
“…Published literature has shown that TAG accumulates under either Si or N limitation [98,109], and in Figure 4 we present a comparison of these conditions with a treatment where the cells were exposed to the microtubule-based cell cycle inhibitor nocodazole. There are several important points to consider from this.…”
Section: The Advantages Of Si Limitation-based Lipid Accumulation Indmentioning
confidence: 99%
“…Cells were cultured in 2 L polycarbonate bottles as described previously (18). Cultures were bubbled with 0.5% CO2 in air (500 mL/min) and maintained at 25°C under constant illumination from fluorescent lamps (photon flux density at the vessel surface averaged over 3600 = 85 ,umol quanta-m-2.…”
Section: Organism and Growth Conditionsmentioning
confidence: 99%